Review of decontamination protocols for shared non-critical objects in 35 policies of UK NHS acute care organizations. (February 2022) - Castelli, A.; Norville, P.; Kiernan, M.; Maillard, J-Y.; Evans, S.L.
Summary: Background: Decontamination of non-critical objects shared by patients is key in reducing hospital-acquired infections (HAIs), but it is a complex process that needs precise guidance from UK National Health Service (NHS) acute care organizations (ACOs). Aim: To review the indications given by NHS ACOs' policies regarding the decontamination of shared non-critical devices. Methods: Detailed lists of decontamination protocols for shared non-critical objects were retrieved from cleaning, disinfection and decontamination policies of 35 NHS ACOs. Three parameters were considered for each object: decontamination method, decontamination frequency, and person responsible for decontamination. Findings: In total, 1279 decontamination protocols regarding 283 different shared non-critical objects were retrieved. Of these, 689 (54%) did not indicate the person responsible for decontamination, and only 425 (33%) were complete, giving indications for all three parameters analysed. Only 2.5% (32/1279) of decontamination protocols were complete and identical in two policies. In policies where cleaning represented the major decontamination method, chemical disinfection was rarely mentioned and vice versa. General agreement among policies was found for four main decontamination methods (detergent and water, detergent wipes, disinfectant wipes, and use of disposable items), two decontamination frequencies (between events and daily) and two responsible person designations (nurses and domestic staff). Conclusions: Decontamination protocol policies for shared non-critical objects had some similarities but did not concur on how each individual object should be decontaminated. The lack of clear indications regarding the person responsible for the decontamination process put at risk the ability of policies to serve as guidance.